Eksploitasi Anak Penghibur Jalanan di Medan: Analisis Hukum Islam dan UU Perlindungan Anak Tahun 2014 - Harahap, Syarif Hidayatullah Agung Raja Dermawan (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This research examines the phenomenon of the exploitation of child street entertainers in Medan through the perspectives of Islamic Law and Law No. 35/2014 on Child Protection. Children are often trapped in situations that force them to work as street entertainers, facing serious physical and psychological risks. The main objective of this research is to identify the factors that cause children to work as street clowns and silver men, and to analyze the views of Islamic Law and national law on this phenomenon. The research methodology used is empirical legal research with field studies, collecting data through documentation, observation, and interviews. The main findings of the research show that economic, social, and cultural factors play significant roles in encouraging children to work on the streets. From the perspective of Islamic Law, the exploitation of child labor is prohibited, and perpetrators may be subject to ta'zir punishment. Meanwhile, according to Law No. 35/2014, the exploitation of child labor is a criminal offense with a maximum penalty of 10 years' imprisonment and a maximum fine of Rp200,000,000. Despite a strong legal foundation, challenges in implementation and oversight remain significant. This research recommends increased collaboration between government agencies, communities, and non-governmental organizations to strengthen child protection and ensure their rights are optimally fulfilled.